2015
DOI: 10.1016/j.virol.2015.02.046
|View full text |Cite
|
Sign up to set email alerts
|

IFI44 suppresses HIV-1 LTR promoter activity and facilitates its latency

Abstract: IFI44 is an interferon-alfa inducible protein, and is associated with infection of several viruses. However, IFI44 elicits minimal antiviral effects on these viruses, and its exact role is still unknown. Here we show that IFI44 inhibits HIV-1 replication in vitro. Through depletion of endogenous IFI44 or overexpression of IFI44 we confirm that IFI44 suppresses HIV-1 LTR promoter activity and affects viral transcription. Furthermore, we find that IFI44 localizes to nuclei and binds to the HIV-1 LTR promoter in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 50 publications
2
67
0
Order By: Relevance
“…While the role of IFI44 is not completely defined, some evidence suggests that this interferon-inducible gene acts as a suppressor of viral replication 24. In the study by Coit et al ,7 hypomethylation of this CpG site was identified when comparing SLE cases with nephritis with healthy controls and was not identified when SLE cases without nephritis were compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…While the role of IFI44 is not completely defined, some evidence suggests that this interferon-inducible gene acts as a suppressor of viral replication 24. In the study by Coit et al ,7 hypomethylation of this CpG site was identified when comparing SLE cases with nephritis with healthy controls and was not identified when SLE cases without nephritis were compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…VSV-G pseudotyped HIV-1 NL4–3 luciferase virus (HIV-1 Luc) or retroviruses expressing HIV-1 Tat (pQCXIP-Tat) were created as described previously (Huang et al, 2015; Power et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Co-immunoprecipitation and western blot analysis was performed as described previously (Huang et al, 2015; Power et al, 2015). Briefly, HeLa cells stably expressing Tat-Flag were treated with levosimendan (10 μM) for 24 hr.…”
Section: Methodsmentioning
confidence: 99%
“…The multiple ifi44 zebrafish genes counts 7 ISG among 19 members, but their two human co-orthologues are induced by type I IFN. Located in the nucleus, IFI44 binds and blocks the HIV1 LTR promoter (56). However, the numerous zebrafish ifi44 probably have sub-functionalized, and mediate multiple antiviral mechanisms.…”
Section: Discussionmentioning
confidence: 99%